Genotyping of Chlamydia trachomatis serovars derived from heterosexual partners and a detailed genomic analysis of serovar F. - Lan, J (1995)
OBJECTIVE--To investigate C trachomatis serovars in contact-traced heterosexual partners. METHODS--Urogenital Chlamydia trachomatis isolates (n = 112) derived from 35 heterosexual patients (index patients) and their 37 chlamydia positive partners (contact patients) were differentiated into serovars by genotyping with restriction fragment length polymorphism (RFLP) analysis of the PCR amplified omp1 gene. In order to investigate whether different strains within the frequently prevalent serovar F were transmitted, two pairs of serovar F (n = 4) were further analysed by genomic DNA fingerprinting with arbitrary primer PCRs (AP-PCRs). RESULTS--Identical C trachomatis serovars were found in 31 of the 35 pairs, serovars E, F, D, and G being most prevalent. In the remaining four pairs different serovars (either D, E, F or G) were found between the index and the contact patients. By AP-PCR analysis the strains of serovar F were found to be identical between the index and the contact patients, but were different between the two pairs in all AP-PCRs used. CONCLUSION--A majority of heterosexual partners, once traced positive for C trachomatis infections, are infected with identical serovars. Identical strains of serovar F found in partners as found by DNA fingerprinting confirms the sexual transmission of C trachomatis.